Hepatitis B virus infection in HIV-positive individuals in the UK collaborative HIV cohort (UK CHIC) study. - Huw Price; Loveleen Bansi; Caroline A Sabin; Sanjay Bhagani; Andrew Burroughs; David Chadwick; David Dunn; Martin Fisher; Janice Main; Mark Nelson; Deenan Pillay; Alison Rodger; et al. (PLoS ONE)
Background Hepatitis B virus (HBV) infection is an increasingly important cause of morbidity and mortality in HIV-infected adults. This study aimed to determine the prevalence and incidence of HBV in the UK CHIC Study, a multicentre observational cohort. Methods and findings 12 HIV treatment centres were included. Of 37,331 patients, 27,450 had at least one test (HBsAg, anti-HBs or anti-HBc) result post-1996 available. 16,043 were white, 8,130 black and 3,277 other ethnicity. Route of exposure was homosexual sex 15,223 males, heterosexual sex 3,258 males and 5,384 females, injecting drug use 862 and other 2,723. The main outcome measures used were the cumulative prevalence and the incidence of HBV coinfection. HBV susceptible patients were followed up until HBsAg and/or anti-HBc seroconversion incident infection, evidence of vaccination or last visit. Poisson regression was used to determine associated factors. 25,973 had at least one HBsAg test result. Participants with HBsAg results were typically MSM (57%) and white (59%) (similar to the cohort as a whole). The cumulative prevalence of detectable HBsAg was 6.9% (6.6 to 7.2%). Among the 3,379 initially HBV-susceptible patients, the incidence of HBV infection was 1.7 (1.5 to 1.9)/100 person-years. Factors associated with incident infection were older age and IDU. The main limitation of the study was that 30% of participants did not have any HBsAg results available. However baseline characteristics of those with results did not differ from those of the whole cohort. Efforts are on-going to improve data collection. Conclusions The prevalence of HBV in UK CHIC is in line with estimates from other studies and low by international standards. Incident infection continued to occur even after entry to the cohort, emphasising the need to ensure early vaccination.